Creating Justice in an Emerging World The Natural Law Basis of Francisco de Vitoria’s Political and International Thought (2017)
This article outlines Francisco de Vitoria’s conception of natural law and natural right in an effort to amend a number of interpretations in the academic literature on his political and international thought that misapprehend Vitoria’s iusnaturalism. In this view, his use of the Thomist doctrine of natural law and justice lays the foundation for his works on politics, society and international relations since the doctrine itself espouses equality and justice both within the domestic realm and between discrete communities. In an implicit appeal to the link between ethics and politics, his doctrine of natural law, moreover, fulfills a critical and constitutional role bydesignating justice and the common good as a pattern of order to which power and authority must conform in order to be legitimate.